2019
DOI: 10.1177/1120672119848277
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of the ab interno gelatin stent in severe pseudoexfoliation glaucoma compared to non-pseudoexfoliation glaucoma at 6 months

Abstract: Purpose: To compare the efficacy and safety of the XEN45 Gel Stent surgery between patients with and without severe pseudoexfoliation glaucoma. Methods: In this retrospective, single-center, comparative chart review, records of 24 eyes of 23 patients with pseudoexfoliation glaucoma and 24 eyes of 23 patients with non-pseudoexfoliation glaucoma with severe glaucoma, defined as uncontrolled intraocular pressure on maximally tolerated medical therapy, were reviewed. All patients were treated with XEN45 Gel Stent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…As a result, PEG exhibited a better survival rate than did POAG in both multivariate (Table 2) and univariate (Fig 3) analyses. This is in an agreement with previous studies reporting favorable clinical results of other MIGS procedures in patients with PEG [38,39]. PEG is a common cause of secondary glaucoma and it is reportedly frequent in many populations [40][41][42][43][44].…”
Section: Plos Onesupporting
confidence: 93%
“…As a result, PEG exhibited a better survival rate than did POAG in both multivariate (Table 2) and univariate (Fig 3) analyses. This is in an agreement with previous studies reporting favorable clinical results of other MIGS procedures in patients with PEG [38,39]. PEG is a common cause of secondary glaucoma and it is reportedly frequent in many populations [40][41][42][43][44].…”
Section: Plos Onesupporting
confidence: 93%
“…Among 14 studies using an absolute dose of 10 µg, the weighted mean average IOP was reduced from 24.4 mm Hg on 2.7 medications at baseline to 15.2 mm Hg on 0.7 medications at the end of follow-up. 5,24,26,[28][29][30][32][33][34][35][36]89,104 Among 21 studies using an absolute dose of 20 µg, the weighted mean average IOP was reduced from 21.6 mm Hg on 2.7 medications at baseline to 14.4 mm Hg on 0.8 medications at the end of follow-up. 5,10,15,21,24,28,33,34,[44][45][46][47][48]50,[54][55][56]60,63,65,68 Only two studies were available with a calculated mean dose of 40 µg; due to the paucity of data, these data are not shown.…”
Section: Interpretationsmentioning
confidence: 99%
“…88 A limited number of studies reported outcomes among eyes diagnosed with POAG compared to PEXG (Table 7). 11,22,36,89,90 Similarly, data are limited but nonetheless encouraging in the setting of uveitic glaucoma. Qureshi et al reported outcomes in an observational case series of 37 eyes with medically uncontrolled glaucoma secondary to uveitis.…”
Section: Interpretationsmentioning
confidence: 99%
“…Multiple recent series have demonstrated the safety and efficacy of XEN gel stent placement at the time of cataract surgery in reducing IOP and IOP lowering medication [35][36][37][38][39][40][41][42]. Interestingly, Widder et al reported that pseudophakic eyes had the most favorable primary success rate compared to phakic eyes and combined surgery with phacoemulsification, and this finding influenced their clinical decision making so as to no longer offer patients combined surgery [43].…”
Section: It Is the Only Currently Available Subconjunctival Migs Devimentioning
confidence: 99%